2017
DOI: 10.1101/221994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell Map of Diverse Immune Phenotypes Driven by the Tumor Microenvironment

Abstract: SUMMARYKnowledge of the phenotypic states of immune cells in the tumor microenvironment is essential for understanding immunological mechanisms of cancer progression and immunotherapy responses, as well as the development of novel treatments. By combining single-cell RNA-seq data from over 45,000 immune cells collected from eight primary breast carcinomas, as well as matched normal breast tissue, peripheral blood, and lymph node, we created an immune map of breast cancer. We developed a preprocessing pipeline,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 104 publications
10
42
0
Order By: Relevance
“…clear separation based on their individual transcriptomes remains difficult. This high overlap of myeloid derived subpopulations mirrors recent findings in breast cancer where previously proposed M1 and M2 macrophage associated genes are frequently expressed within the same cells among these two clusters[48]. As Azizi et al, describes, this suggests that distinct prototypical macrophages may not be prevalent within tumors and may in fact exist within the spectrum of these two phenotypes.…”
supporting
confidence: 78%
“…clear separation based on their individual transcriptomes remains difficult. This high overlap of myeloid derived subpopulations mirrors recent findings in breast cancer where previously proposed M1 and M2 macrophage associated genes are frequently expressed within the same cells among these two clusters[48]. As Azizi et al, describes, this suggests that distinct prototypical macrophages may not be prevalent within tumors and may in fact exist within the spectrum of these two phenotypes.…”
supporting
confidence: 78%
“…[35] Recent studies have also revealed an unprecedented heterogeneity within T-cell and myeloid cell types, where subsets of these exhibited a diverse spectrum of states. [19,36,37] These states present as complex phenotypes not mainly defined by marker genes, but rather the expression profile of a larger gene set. When the finer tiers of these two cell types were examined, several trends of co-localization could be observed; such as weak positive signals between cDC2:CD1C, Mø1:EGR1, and pDC:IRF7 with several CD4+ T-cell populations, including…”
Section: Trends Of Cell Type Co-localizationmentioning
confidence: 99%
“…scRNA-seq libraries were prepared according to 10X Genomics specifications. The Sequence Quality Control (Azizi et al, 2018) package was used to process raw scRNA-seq reads to a transcript count matrix, including de-multiplexing, alignment, barcode and UMI error correction, and generation of a digital expression matrix. Alignment was performed to the hg38 annotation restricted to transcribed, polyadenylated RNA of length >200 nucleotides to increase mapping specificity.…”
Section: Scrna-seqmentioning
confidence: 99%